A novel peroral digital cholangioscope with a large accessory channel: An experimental study. (15th September 2022) - Tonozuka, Ryosuke; Itoi, Takao; Nagai, Kazumasa; Sofuni, Atsushi; Tsuchiya, Takayoshi; Ishii, Kentaro; Tanaka, Reina; Mukai, Shuntaro; Minami, Hirohito; Yamamoto, Kenjiro
Abstract: Background/Purpose: A peroral cholangioscope (POCS) can allow direct visualization of the biliary mucosa and its use is becoming more widespread due to improvements in functionality, image quality, and operability, as well as the development of related devices. Recently, a novel mother‐baby peroral cholangioscope (nMB‐POCS) with a large (2‐mm) accessory channel has been developed. In this study, we evaluated the feasibility of this novel POCS in a dry simulation and animal model. Methods: We evaluated the ease of insertion and maneuverability of the nMB‐POCS, the image quality, and the passage of the devices into the accessory channel and into the common bile duct in a dry and live porcine model. Results: In both models, the nMB‐POCS could be easily inserted into the duodenoscope and into the distal bile duct and hilum. The image quality was good, and it was possible to observe the surface structure and the vascular network of the bile duct mucosa in detail. Conclusions: The nMB‐POCS with its larger accessory channel is expected to improve the efficiency of diagnosis and  treatment,  and reduce the procedure time. Clinical studies in patients are warranted. Abstract : Tonozuka et al. evaluated the feasibility of a novel mother‐baby peroral cholangioscope with a large accessory channel of 2 mm in diameter in a dry simulation model and a live porcine model. Maneuverability, image quality, and usability with several endoscopic retrograde cholangiopancreatography devices were good, demonstrating its potential for clinical practice.